Translation and validation of the Shona version of the exercise benefits and barriers scale in Zimbabwean adult people living with HIV/AIDS : a cross-sectional study - Dambi, Jermaine Matewu (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.